PENINGKATAN KUALITAS PEMBELAJARAN MATEMATIKA GURU SMP MELALUI SOAL-SOAL HIGHER ORDER THINKING SKILLS (HOTS) DI KABUPATEN BOGOR, PROVINSI JAWA BARAT - Ibnu Hadi Hadi; Yudi Mahatma; Debby Agustine; Andita Sulistyaningrum (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2021)
Abstract This paper discusses how to improve the quality of mathematics learning for junior high school (SMP) teachers through training that discusses High Order Thinking Skills (HOTS) questions. As is known, the 2013 curriculum that uses a scientific approach will force the learning process to be more dynamic. Teachers and students will try to go through a process that is adapted to the curriculum. Related to this, HOTS type questions will appear. In junior high school mathematics learning, questions of this type will be discussed, studied, deepened and hopefully will become a good habit. Based on Bloom's taxonomy, the characteristics of the HOTS questions are included in the criteria for analyzing, assessing and creating. If teachers are accustomed to working on and making HOTS type questions, of course they will think differently in doing their learning. The process of delivering and teaching these questions will be good if the teachers understand their characteristics. For this reason, the introduction and training of HOTS questions is needed so that teachers have sufficient ability to provide learning, especially related to HOTS material. With the training on HOTS questions, it is hoped that there will be an increase in the ability of learning mathematics for junior high school teachers. Responses from junior high school teachers to this training were delivered through questionnaires before and after the training. From the questionnaires submitted, the teachers at least gained additional knowledge and began to be able to identify the types of questions that were of the HOTS type. Abstrak Tulisan ini membahas bagaimana peningkatan kualitas pembelajaran matematika pada guru-guru Sekolah Menengah Pertama (SMP) melalui pelatihan yang membahas soal-soal High Order Thingking Skills (HOTS). Seperti yang diketahui, kurikulum 2013 yang menggunakan pendekatan saintifik akan “memaksa” proses pembelajaran menjadi lebih dinamis. Guru maupun siswa akan berusaha menjalani proses yang disesuaikan dengan kurikulum tersebut. Terkait hal itu, akan muncul soal-soal berjenis HOTS. Pada pembelajaran matematika tingkat SMP, soal jenis ini akan dibahas, dipelajari, diperdalam dan harapannya akan menjadi suatu “kebiasaan” yang baik. Berdasarkan taksonomi Bloom, karakteristik soal HOTS masuk pada kriteria menganalisis, menilai dan mengkreasi. Jika para guru terbiasa mengerjakan dan membuat soal tipe HOTS, tentunya mereka akan berpikir “berbeda” dalam melakukan pembelajarannya. Proses penyampaian dan pengajaran soal-soal ini akan menjadi baik jika para guru paham mengenai karakteristiknya. Untuk itu, pengenalan dan pelatihan soal HOTS ini diperlukan agar para guru memiliki kemampuan yang cukup untuk memberikan pembelajaran khususnya terkait materi HOTS. Dengan adanya pelatihan soal-soal HOTS, diharapkan terjadi peningkatan kemampuan pembelajaran matematika pada guru-guru SMP. Tanggapan dari guru SMP terhadap pelatihan ini disampaikan melalui kuesioner sebelum dan setelah pelatihan. Dari kuesioner yang disampaikan, para guru setidaknya mendapatkan tambahan pengetahuan dan mulai bisa mengidentifikasi jenis soal yang bertipe HOTS.